Faktor-faktor yang mempengaruhi siswa smkn jurusan pariwisata di kota denpasar dalam memilih perguruan tinggi - A.A. Manik Pratiwi; Putu Diah Kesumadewi (Jurnal Kepariwisataan dan Hospitalitas, 2021)
Abstract In line with the increasing interest of students of SMKN majoring in tourism who continue to higher education, this study aims to determine the factors that influence SMKN students majoring in Tourism in Denpasar City in choosing universities and to find out the most dominant factors in influencing SMKN students majoring in Tourism in the City. Denpasar in choosing higher education institutions. This study used 100 respondents with accidental sampling technique. The data will be analyzed using quantitative descriptive analysis and using factor analysis. Based on the results of calculations using factor analysis, there are 21 variables which are grouped into 5 factors, namely the motivation factor plus the flexible lecture time factor and employees, the college physical evidence factor plus the people factor and the good image variable, the price factor and good accreditation. , reference group factors plus personal factors, and the latest curriculum variables. Of the five factors, the motivation factor plus the flexible lecture time factor and employees are the most dominant factors. Higher education institutions need to carry out promotional activities to SMK so that Vocational School students know the profile of the Higher Education, which will later become a reference for SMK students in choosing Higher Education Keywords: Factor analysis, Selection of Higher Education, Vocational School Students majoring in Tourism